Can an impulsive variation of the solar wind plasma pressure trigger a plasma bubble? A case study based on CSES, Swarm and THEMIS data. Issue 1 (1st January 2021) - Piersanti, M.; Pezzopane, M.; Zhima, Z.; Diego, P.; Xiong, C.; Tozzi, R.; Pignalberi, A.; D'Angelo, G.; Battiston, R.; Huang, J.; Picozza, P.; Rui, Y.; et al.
Abstract: During the August 25, 2018 geomagnetic storm, the new borne CSES-01 satellite and the Swarm A satellite detected a really large equatorial plasma bubble (EPB) in the post-midnight sector over western Africa. We investigated the features of this deep ionospheric plasma depletion using data from the Langmuir probes on-board CSES-01 and Swarm A satellites, and data from the high-precision magnetometer and the electric field detector instruments on-board CSES-01. Using also plasma and magnetic field data from THEMIS-E satellite we found that, during the passage of the magnetic cloud that drove the geomagnetic storm, an impulsive variation lasting about ten minutes characterized the solar wind (SW) pressure. The analysis of the delay time, between the occurrence of such impulsive variation and the detection of the plasma bubble, suggests a possible link between the SW pressure impulsive variation as identified by THEMIS-E and the generation of the EPB as detected by CSES-01 and Swarm A. We put forward the hypothesis that the SW pressure impulsive variation might have triggered an eastward prompt penetrating electric field that propagated from high to equatorial latitudes, overlapping in the nightside region to the zonal westward electric field, causing either a reduction or an inversion, at the base of the EPB triggering.